Attitudes toward Statistics and Statistical Literacy of Public Senior High School Students - Reynaldo E. Repedro, Jr.; Crispina V. Diego (Philippine Social Science Journal, 2021)
Statistics has proven its usefulness in research over centuries to produce quality insights and data-driven decision-making. Learning statistics not only rely on cognitive but other factors such including attitude as well. This descriptive-correlational research determined the attitudes toward statistics in the components of affect, cognitive competence, value, difficulty, interest and effort, and statistical literacy of 200 public senior high school students selected through stratified random sampling. The SATS-36© developed by Schau et al. (2003) was used to determine attitudes, while a researcher-made questionnaire was utilized to measure statistical literacy. Using descriptive statistics and inferential analysis, students' attitudes toward the subject were established positively in value, interest, and effort components. In contrast, a negative attitude was exhibited in the components of affect, cognitive competence, and difficulty. Students' statistical literacy was found to be low in all areas and as a whole. Among the six components of attitude, the value component showed a significant relationship and predicted students' statistical literacy. Thus, the most vital component of attitudes toward statistics is value.